Smartphone-based evaluation of static balance and mobility in long-lasting COVID-19 patients - Corrêa, Bruna Danielle Campelo; Santos, Enzo Gabriel Rocha; Belgamo, Anderson; Pinto, Gustavo Henrique Lima; Xavier, Stanley Soares; Silva, Camilla Costa; Dias, Ápio Ricardo Nazareth; Paranhos, Alna Carolina Mendes; Cabral, André dos Santos; Callegari, Bianca; Costa e Silva, Anselmo de Athayde; Quaresma, Juarez Antônio Simões; et al. (Frontiers in Neurology, 2023)
Background: SARS-CoV-2 infection can lead to a variety of persistent sequelae, collectively known as long COVID-19. Deficits in postural balance have been reported in patients several months after COVID-19 infection. The purpose of this study was to evaluate the static balance and balance of individuals with long COVID-19 using inertial sensors in smartphones.Methods: A total of 73 participants were included in this study, of which 41 had long COVID-19 and 32 served as controls. All participants in the long COVID-19 group reported physical complaints for at least 7 months after SARS-CoV-2 infection.Participants were evaluated using a built-in inertial sensor of smartphone attached to the low back, which recorded inertial signals during a static balance and mobility task (Timed Up and Go test). The parameters of static balance and mobility obtained from both groups were compared.The groups group were matched for age and BMI. Of the 41 participants in the long COVID-19 group, 22 reported balance impairment, and 33 had impaired balance in the Sharpened Romberg test. Static balance assessment revealed that the long COVID-19 group had greater postural instability with both eyes open and closed than the control group. In the TUG test, the long COVID-19 group showed greater acceleration during the sit-to-stand transition compared to the control group.The smartphone was feasible to identify losses in the balance motor control and mobility of patients with long-lasting symptomatic COVID-19 even after several months or years. Attention to the balance impairment experienced by these patients could help prevent falls and improve their quality of life and the use of the smartphone can expand this monitoring for a broader population.